Necessity of selective neck dissection for T1-2N0 TSCC patients: a retrospective cohort study - Guanzheng Chen; Xiangpan Kong; Zhien Feng; Jia Kang; Zhengxue Han; Bo Li (BMC Oral Health)
Abstract Background This study aimed to assess the prognosis of T1-2N0 stage tongue cancer patients who underwent surgery for the primary lesion without elective neck dissection and to identify the risk factors for prognosis. Methods We retrospectively analyzed early-stage tongue cancer patients in our center. Statistical analyses were performed using SPSS and R software. Results The study reviewed 168 patients, revealing a 3-year overall survival rate of 90.5%, a 3-year cervical lymph node metastasis-free survival rate of 73.2%, and a 3-year disease-specific survival rate of 89.3%. A depth of invasion of 3 mm showed significant prognostic value for overall survival (P = 0.001), cervical lymph node metastasis-free survival (P = 0.002), and disease-specific survival (P < 0.001). Patients were categorized into four subgroups (thick T1, thin T1, thick T2, and thin T2) to further explore the prognostic significance of depth of invasion across different T stage categories. The combination of T stage and a 3 mm depth of invasion demonstrated significant prognostic value in univariate analysis for overall survival (P = 0.002), cervical lymph node metastasis-free survival (P = 0.010), and disease-specific survival (P < 0.001). COX regression analysis confirmed the statistical significance of T stage combined with a 3 mm depth of invasion for overall survival (OR = 10.653; 95% CI, 2.394 to 47.404; P = 0.002) and lymph node metastasis-free survival (OR = 3.016; 95% CI, 1.365 to 6.667; P = 0.006). Conclusions The findings highlight depth of invasion and T stage as key prognostic factors in early-stage tongue squamous cell carcinoma. Consideration of elective neck dissection is advised for patients with T2 tumors and a depth of invasion exceeding 3 mm to potentially enhance their prognosis. Trial registration The current research was registered in Chinese Clinical Trial Registry on April 8, 2021. The trial registration number is ChiCTR2100045188.